Hemoglobin mass, blood volume and VO2max in prepubertal cross-country skiers - Aaeng, A.; Landgraff, H. W.; Hallén, J. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: In adults, a high aerobic power (VO2max) is associated with a high hemoglobin mass (Hbmass) (Eastwood et al. 2011) and males has higher values than females for both variables. This study aims to identify if gender differences in Hbmass, blood volume (BV), and VO2max also exist in a group of prepubertal Norwegian cross- country skiers and if Hbmass and VO2max are associated. Methods: Subjects were 72 Norwegian children (boys n= 46, age 11.9 ± 0.3 and girls n=26, age 11.8 ± 0.2) recruited from cross-country ski clubs. Hbmass and BV were measured by the optimized CO-rebreathing method. Venous blood was sampled from an antecubital vein. VO2max was determined by incremental treadmill running to exhaustion. Height, body mass and percentage of body fat (bioimpedance) were measured. Results: Heights were 151 ± 7 and 154 ± 7 cm, weights were 39.2 ± 4.9 and 41.0 ± 6.0 kg and body fat were 12% ± 6% and 13% ± 4% for boys and girls, respectively, with no significant differences between genders. Hemoglobin concentrations were 132 ± 69 and 132 ± 57 g/l, Hbmass were 406 ± 57 and 400 ± 56 g and BV were 3370 ± 490 and 3340 ± 490 ml in boys and girls, with no differences between genders. Relative to body mass, both Hbmass (10.3 ± 0.8 vs. 9.8 ± 0.8 g/kg, p = 0.02) and BV (86 ± 2.7 vs. 82 ± 6.1 ml/kg, p = 0.01) were higher in boys than girls. Also VO2max was higher (65 ± 6.3 vs. 59 ± 5.1 ml/kg/min, p < 0.001) and time to exhaustion was longer (6.13 ± 1.15 vs. 5.31 ± 0.94 min, p = 0.003) in boys. There was a significant correlation between absolute VO2max (L/min) and Hbmass (g) (r= 0.70) (boys and girls combined) and the correlations were similar for both genders. The correlation for relative values between VO2max (ml/kg/min) and Hbmass (g/kg) was weaker (r= 0.52) Discussion: In prepubertal cross-country skiers (11,9 years), height, weight and body fat were similar in boys and girls. However, Hbmass, BV and VO2max relative to body mass were 5%, 5% and 10% higher in boys, respectively. There were significant correlations between Hbmass and VO2max both for absolute and relative values, but these correlations were lower than correlations normally found in adults. This is probably, at least partly, due to larger coefficient of variation for these measurements in children compared to for adults. Hence, it is likely that VO2max are influenced by Hbmass also in prebubertal children.